A RUSSIAN PROTECTORATE OVER SOUTH AFRICA? (Historia, 2021)
Few historians in the West and in this country in particular, know that a South African general* approached the Russian government with a request for help to start a native rising in South and Central Africa. He was prepared to organise it and hoped that it would lead to a general revolt, joined in by the whites, which would result in the defeat of the English, the end of British rule and the eventual establishment of a Russian Protectorate over South Africa -"A jewel worthy of the crown of Russia." At first glance even the suggestion of such a move being made seems either an unwarrantable allegation or the action of a madman. However, the event is a histo-rical fact, which took place in February 1905. The reason why there was no mention of it in any official records was because the negotiations were secret, carefully concealed at the time and the files containing them were only discovered sometime after the Russian Revolution. The originals of the documents quoted are now kept among the records of the Ministry of Foreign Affairs in Moscow.
Keywords: British rule; Pienaar, F.; South Africa; Russian Protectorates; Joubert-Pienaar, F; History